A Comparison of the Mora-Vahrson Methodology and the Morphometric Method to Determine Areas Susceptible to Landslides in the Macho River Microbasin, Costa Rica - Quesada Román, Adolfo; Feoli-Boraschi, Sergio (Revista Geográfica de América Central., 2018)
The Mora-Vahrson methodologies (1994) and the morphometric method are analyzed to study their strengths and weaknesses in the identification of areas susceptible to landslides. First, these methodologies are explained; later, a case study is conducted in the Rio Macho microbasin, northeast San Jose, to compare the results of both methods. This analysis establishes that both methodologies are useful for the determination of baseline for zoning areas susceptible to landslides, depending on the availability of inputs. Finally, these tools can be used for disaster risk management by slope processes and territorial planning.